2021
DOI: 10.18805/lrf-640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Doses of Poultry Manure Application on Yield Components and Yield of Different Faba Bean (Vicia faba L.) Varieties

Abstract: Background: A study was conducted to determine the effects of different doses of poultry manure application on the yield and some yield components of faba bean crop under ecological conditions of Siirt province, Southern Eastern Anatolian Region of Turkey. Methods: The study was carried out in randomized complete block design with 3 replications. The main plots were varieties and the sub-plots were poultry manure doses. At 15 days prior to sowing, 0 (control), 500, 1000, 1500 kg ha-1 of poultry manure was spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The greenness index of leaves is determined by the availability of nutrients—mainly nitrogen, as well as thermal and humidity conditions [ 12 ], therefore, it should be assumed that the application of the PMs, of which determines the change in these conditions, will correlate with the SPAD index. Overdosing of PM may lead to over-saturation of the soil, which may be a factor limiting the nutrient uptake by the plant [ 8 , 13 ]. Some studies showed a positive effect of PM on the physical and chemical properties of soil as a result of its combined use with biochar [ 6 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The greenness index of leaves is determined by the availability of nutrients—mainly nitrogen, as well as thermal and humidity conditions [ 12 ], therefore, it should be assumed that the application of the PMs, of which determines the change in these conditions, will correlate with the SPAD index. Overdosing of PM may lead to over-saturation of the soil, which may be a factor limiting the nutrient uptake by the plant [ 8 , 13 ]. Some studies showed a positive effect of PM on the physical and chemical properties of soil as a result of its combined use with biochar [ 6 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%